Stable room temperature magnetic ordering and excellent catalytic activity of mechanically activated high surface area nanosized Ni0.45Zn0.55Fe2O41. Issue 96 (17th October 2015) - Dey, S.; Gomes, R.; Mondal, R.; Dey, S. K.; Dasgupta, P.; Poddar, A.; Reddy, V. R.; Bhaumik, A.; Kumar, S.
<x xml:space="preserve">Abstract</x> Mechanosynthesized nanometric Ni0.45Zn0.55Fe2O4 exhibit stable magnetic ordering at room temperature, excellent catalytic property and memory effect in dc magnetization profile.